Konseling Dan Pengembangan Karir PNS: Literature Review - Saut Gracer Sijabat (FAI- Undar, 2022)
The purpose of this article is to describe several forms of career counseling services that can be adopted in the implications of civil servant management in central and local government agencies considering that career development is one form of civil servant management as regulated in Law Number 11 of 2017 concerning Civil Servant Management. However, career development does not always go well, various problems faced by employees can be an obstacle to career development. Career counseling as a service that aims to overcome employee problems is expected to be able to help so that the mandate of the Law can be achieved. Counseling aims not only to address pathological problems and provide interventions for those with mental health challenges but also includes the goals of promoting health, personal growth, education, and career development. The method used in this article is to use a Systematic Literature Review involving 15 documents from 2012 to 2018 and to identify 3 forms of career counseling services that are relevant to the management of civil servants, including civil servant career transition counseling, counseling for civil servants with disabilities, counseling for elderly civil servants.